2013
DOI: 10.1007/s13760-013-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

Pioneers in migration, pioneering in dementia: first generation immigrants in a European metropolitan memory clinic

Abstract: By reviewing the clinical files of 1,058 consecutive newly admitted outpatients of a Brussels-based memory clinic between 2005 and 2012, this study aims to document the demographic and clinical characteristics of European and non-European first generation immigrants. They accounted for 18.6% of the patients, of which 8.6% came from outside Europe (mostly from Morocco, Turkey and the Democratic Republic of Congo). Immigrants with AD tended to be younger, and there was a higher proportion of males among non-Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 12 publications
1
44
0
1
Order By: Relevance
“…Dementia coordinators in the present study mainly reported working with ME service users originating from the Middle East, East Europe, and South Asia, who were generally in the moderate to severe stage of their dementia disorder at the point they met them. As discussed in the previous reports, this may be an indication that people from these ME communities are less able to access dementia care and support services, and when they do so, they access these services at a later stage of the disease (Cooper et al, 2010;Hailstone, Mukadam, Owen, Cooper, & Livingston, 2017;Mukadam, Cooper, Basit, & Livingston, 2011a;Naess & Moen, 2015;Pham et al, 2018;Segers et al, 2013;van Wezel et al, 2016). Whereas some barriers to accessing post-diagnostic dementia care and support seem to be associated with specific cultural norms and values in predominantly family-oriented Middle Eastern, East European, and South Asian ME communities, others seem to represent more general barriers faced by minority groups in a society where only mainstream services tailored to the majority culture and language are available.…”
Section: Discussionmentioning
confidence: 94%
“…Dementia coordinators in the present study mainly reported working with ME service users originating from the Middle East, East Europe, and South Asia, who were generally in the moderate to severe stage of their dementia disorder at the point they met them. As discussed in the previous reports, this may be an indication that people from these ME communities are less able to access dementia care and support services, and when they do so, they access these services at a later stage of the disease (Cooper et al, 2010;Hailstone, Mukadam, Owen, Cooper, & Livingston, 2017;Mukadam, Cooper, Basit, & Livingston, 2011a;Naess & Moen, 2015;Pham et al, 2018;Segers et al, 2013;van Wezel et al, 2016). Whereas some barriers to accessing post-diagnostic dementia care and support seem to be associated with specific cultural norms and values in predominantly family-oriented Middle Eastern, East European, and South Asian ME communities, others seem to represent more general barriers faced by minority groups in a society where only mainstream services tailored to the majority culture and language are available.…”
Section: Discussionmentioning
confidence: 94%
“…Only one study used the shortened version of the Comprehensive Assessment and Referral Evaluation (Short-CARE) to identify persons with dementia [ 43 ]. Three studies did not specify the criteria that was used for dementia diagnosis [ 38 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies found that immigrants had poorer cognitive function compared to individuals in hosting countries that are native-born residents [ 39 , 40 , 45 , 48 , 52 ]. One study showed that a higher proportion of immigrants scored as “cognitively impaired” measured by the CAMDEX [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the US, a retrospective cohort study of 1,789 Hispanic-American participants indicated no association between migration and cognitive function [17]. Another study of 1,085 participants in Europe observed poorer cognitive function in non-European migrants than in local citizens [18]. In China, a 12-year longitudinal study indicated that rural-to-urban and rural residents exhibited more rapid declines in cognitive function than urban residents [19].…”
Section: Introductionmentioning
confidence: 99%